Four Monoterpene Compounds: Repellency Evaluation Against Aedes aegypti - Zaki Z, Mohd; Ali N. A, Mohd; A. S, Ahmad; Patah M. F, Zoll.; H, Hassan; Jamil I. K, Mohd; Bakar S. A, Abu (Malaysian Journal of Science, 2005)
Repellency activity has attracted scientist in accordance of their usefulness as a control against vector mosquito. It can provide protection against the insects bite especially insects of public health importance. Repellency was defined as the stimulation by a chemical of oriented movements away from the source, or the prevention of the insect from approaching the source. Of such interest, four monoterpene compounds, i.e., citronellal, citronellol, geraniol and limonene were tested individually for their repellency activity against adult female vector mosquito of dengue and dengue heamorrhagic fever, Aedes aegypti. Repellency activity was evaluated using repellency kit with human as volunteers. Results indicated that citronellol gave the strongest activity with median effective concentration value (ECÃ¢â€šâ€¦Ã¢â€šâ‚¬) of 0.00011 mg cmÃ¢ÂÂ»Ã‚Â². It was followed by geraniol (0.00018 mg cmÃ¢ÂÂ»Ã‚Â²), citronellal (0.00025 mg cmÃ¢ÂÂ»Ã‚Â²) and limonene (0.00268 mg cmÃ¢ÂÂ»Ã‚Â²). Standard repellent deet was also evaluated for the repellency activity and gave ECÃ¢â€šâ€¦Ã¢â€šâ‚¬ value of 0.0005 mg cmÃ¢ÂÂ»Ã‚Â². This paper then provides information on the repellency activity of the four commercial monoterpenes, which could be found abundantly in the essential oil of plaat kingdom.